ANALYSIS OF DOCUMENT EXAMINATION AND DETERMINATION OF IMPORT TARIFFS AND FREE TRADE FACILITY SCHEMES AT THE BELAWAN TMP KPPBC FOR IMPORTS (International Journal of Cultural and Social Science, 2026)
Import duties are state levies on imported goods in accordance with applicable laws. Imported goods are then subject to tariffs based on the classification of the goods. Import document inspection officials conduct inspections based on applicable regulations, namely Law Number 17 of 2006 concerning Customs and its derivative regulations, namely the Regulation of the Minister of Finance and the Regulation of the Director General of Customs and Excise. This paper will examine the effectiveness of the procedures and stages of import document inspection implemented by the Belawan Customs and Excise Service Office (KPPBC TMP) and the inhibiting factors in ensuring compliance with customs regulations. This paper uses a qualitative method approach. Data collection techniques include observation, interviews, and documentation, which are then analyzed using the techniques of Miles & Huberman (1992: 16). The results of this paper indicate that the procedures and stages of import document inspection at the Belawan Customs and Excise Service Office (KPPBC TMP) have been quite effective through the implementation of an electronic-based service system and risk management. Inhibiting factors found include importers' low understanding of customs regulations, misclassification of goods, constraints on electronic systems, high volume of import activities, and additional inspections of goods considered high risk.